2014
DOI: 10.1371/journal.pone.0106845
|View full text |Cite
|
Sign up to set email alerts
|

Organ Donation in Switzerland - An Analysis of Factors Associated with Consent Rate

Abstract: Background and AimSwitzerland has a low post mortem organ donation rate. Here we examine variables that are associated with the consent of the deceased’s next of kin (NOK) for organ donation, which is a prerequisite for donation in Switzerland.Methods and AnalysisDuring one year, we registered information from NOK of all deceased patients in Swiss intensive care units, who were approached for consent to organ donation. We collected data on patient demographics, characteristics of NOK, factors related to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
1
22
0
3
Order By: Relevance
“…Time impacts upon the ODT process in two ways (Abidin et al., ; De Groot et al., ). These are as follows: (i) its (in)appropriateness (with reference to when requests are made); and, (ii) its (in)adequacy (with regard to time allocated for making any such requests; De Groot et al., ; Weiss, Coslovsky, Keel, Immer, & Juni, ).…”
Section: Resultsmentioning
confidence: 99%
“…Time impacts upon the ODT process in two ways (Abidin et al., ; De Groot et al., ). These are as follows: (i) its (in)appropriateness (with reference to when requests are made); and, (ii) its (in)adequacy (with regard to time allocated for making any such requests; De Groot et al., ; Weiss, Coslovsky, Keel, Immer, & Juni, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies show significant impact of socioeconomic variables on WTD , there is lack of consensus on the sign of influence. Evidence from Switzerland shows education as a significant predictor of organ donation, but others show no such link . Another study on Canada found a positive link between income and WTD .…”
Section: Literature Reviewmentioning
confidence: 99%
“…We used the following hospital level information: presence of an angiography device; full-time equivalent (FTE) of the physicians by 1,000 cases (grouped into tertiles); type of hospital region (urban or rural); language region of the hospital (German, French or Italian); and the number of hospital stays per year. As has been done previously [ 10 ], we divided hospitals into three groups: small-volume (<15,001 cases/year), medium-volume (15,001–30,000 cases/year) or high-volume (> 30,000 cases/year) volume.…”
Section: Methodsmentioning
confidence: 99%